Bem-estar psicológico de servidores e funcionários técnico-administrativos das Instituições de Ensino Superior Públicas e Privadas : indicadores e antecedentes - Andrade, Palloma Rodrigues de (2008)
The elaboration of this thesis aimed at getting to know the structure of the psychological well-being (PWB) at work and analysing the differences in the PWB levels among technical-administrative servants in public and private Institutions of Higher Education (IES) in the municipality of João Pessoa. Two hundred and thirty-three public and private IES male and female servants of João Pessoa participated in the research, replying to an instrument composed of questionnaires referring to the elaborated model. Factorial and regression analyses were accomplished in order to test the hypotheses in respect of the proposed model. The results showed that the PWB related with the work is composed of indicators such as affection, vitality, anxiety, depression, satisfaction at work and aspiration for accomplishment and reduction of the self-efficiency. The observed PWB predictors at work were the IES type, presence of children, age and the escape and back-out facing strategy. These predictors possess relationship of moderation among them in the explanation of PWB. On comparing the PWB experienced by the technical-administrative servants, it was observed that those linked to private IES showed higher PWB rates. Furthermore, there are differences among PWB predictors in accordance with the IES type. The applicability of the results of this thesis is wide as regards social interventions in the search of health improvement under a psycho-sociological perspective. Eventually, the thematic of this thesis intends to reinforce the studies on the worker s health, since by knowing what would lead him into a feeling of accomplishment and well-being will result in more chances of promoting him, while creating opportunities of a sounder life for these people in psychological terms